Enhancing Arabic Speaking Skills Through AI-Assisted Adaptive Vocabulary Games: Evidence from a Classroom Intervention - Cahaya Tuw Fajardini; Sri Wahyuningsih; Nurul Zuhriyah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
The development of Arabic speaking skills remains a significant challenge for many secondary school learners, particularly due to limited vocabulary mastery and insufficient opportunities for meaningful oral communication. This study investigates the effectiveness of AI-assisted adaptive vocabulary games in enhancing Arabic speaking skills among secondary school students. Using a classroom intervention design conducted in two instructional cycles, the study involved 31 tenth-grade students at MA Muhammadiyah Kota Bima, Indonesia. Data were collected through speaking performance tests, classroom observations, and learning documentation. The findings revealed a consistent improvement in students’ speaking performance, as indicated by an increase in the mean score from 62 in the pre-intervention stage to 68 in Cycle I and 76.25 in Cycle II. Learning mastery also increased substantially from 16.7% to 80.64% by the end of the intervention. Furthermore, the N-Gain score of 0.375 indicated a moderate level of effectiveness. The findings suggest that vocabulary-centered interactive activities can facilitate oral language production by promoting contextual vocabulary use and repeated speaking practice. From an adaptive learning perspective, the study highlights the potential of integrating Generative Artificial Intelligence into vocabulary game design to support more personalized and communicative Arabic language learning environments. The study contributes to the growing discourse on AI-enhanced language learning by demonstrating the pedagogical value of adaptive vocabulary-based interventions for developing Arabic speaking skills.